Identification of Etiological Agents of Pyogenic Meningitis by Gram Stain Culture in the Patients Admitted in Two Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Bacterial meningitis is an important cause of mortality and long termmorbidity. Early and accurate diagnosis of bacterial meningitis is of criticalconcern.The bacterial meningitis epidemiological landscape is not static andetiological agent varies with age and immune status and different geographic area.A simple Gram stained smear can offer immediate clues to aid the diagnosis ofpyogenic meningitis. This study was performed to identify the causative agents ofpyogenic meningitis.Materials and methods: This cross sectional study was carried out in theDepartment of Microbiology, Chattogram Medical College for cytologicalexamination, biochemical tests, Gram’s stain, culture. The gold standard fordiagnosis of any infection including meningitis is the isolation and identification ofthe causative agent.Results: Among the 144 suspected meningitis cases, according to cytological andbiochemical findings 36 (25%) were categorized as probable bacterial meningitiscases and 68(47.22%) cases were viral meningitis, normal level of protein, glucoseand cell count were found in 40 (27.78%) cases. Among the 36 cases of probablebacterial meningitis, culture was positive in 12 (33.33%) and Gram’s stain waspositive in 9 (25%) cases. Streptococcus pneumoniae was the predominent organismdetected by isolation in 6(50%).Conclusion: S. pneumoniae is the predominant cause of pyogenic meningitis.Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 24-27